Locus-of-hope in therapeutic communities for addiction: Testing the framework, feasibility, and efficacy of a brief intervention - Ramos, Sixtus Dane A. (Animo Repository, 2023)
The therapeutic community (TC) is a social-learning treatment platform widely used for substance use disorders. Most studies focused on the TC's contribution to recovery and less on personal dispositions that interact with its treatment process. The current research argues that the person’s locus-of-hope can boost the TC mechanism, and an intervention based on locus-of-hope can enhance TC outcomes. Following a framework for developing and evaluating complex interventions, three independent and complementary studies were done to test the brief locus-of-hope intervention’s theoretical framework, feasibility, and efficacy. Study 1 examined if locus-of-hope boosted how community process experience predicted recovery capital and psychological well-being through group working alliance. Participants with high internal and external-peer locus-of-hope reported nonsignificant indirect pathways. For participants with high external-family and external spirit locus-of-hope, the indirect pathways to recovery capital and psychological well-being were significant. Based on the locus-of-hope model of TCs and hope-based therapy components, a brief locus-of-hope intervention was developed. Study 2 then assessed the feasibility of the brief locus-of-hope intervention. Participants found the brief intervention acceptable, appropriate, and feasible, with some limitations that can be addressed in future iterations of the protocol. Lastly, Study 3 tested the brief locus-of-hope intervention’s efficacy using a randomized clinical trial with pre-treatment, post-treatment, and follow-up design (RCT-PPF). Participants who received the brief locus-of-hope intervention reported significant improvements in internal locus-of-hope, external-peer locus-of-hope, community process experience, and group working alliance compared to the control group across time, but not for family hope, spiritual hope, recovery capital, and psychological well-being. The brief locus-of-hope intervention also did not moderate the TC mechanism. But based on partial least squares structural equation modelling (PLS-SEM), the brief locus-of-hope intervention indirectly boosted residents’ recovery capital and psychological well-being by path of community process experience to group working alliance at post-treatment. The brief locus-of-hope intervention’s indirect pathways were maintained for residents’ recovery capital but not for psychological well-being at 1-month follow-up. The overall findings offer preliminary evidence for the locus-of-hope model’s validity in TCs and the brief locus-of-hope intervention’s feasibility and efficacy. Insights from these results are expounded, and implications on TC practice, locus-of-hope research, and positive interventions in substance use disorder treatment in the Philippine context are discussed.